2015
DOI: 10.1111/exd.12704
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐α‐trypsin inhibitor heavy chain 5 (ITIH5) is overexpressed in inflammatory skin diseases and affects epidermal morphology in constitutive knockout mice and murine 3D skin models

Abstract: Inter-α-trypsin inhibitors are protease inhibitors that are thought to be important regulators in various acute-phase processes. They are composed of one light chain (bikunin) and different heavy chains (ITIHs). The only function known so far of ITIHs is the covalent linkage to hyaluronan (HA). As there is virtually no knowledge on the distribution and function of ITIH proteins in skin tissue, we performed a systematic characterization of ITIH expression in healthy and diseased skin. Using GeneChip(®) Human Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 34 publications
0
43
0
1
Order By: Relevance
“…Moreover, during many inflammatory events, the ITIH–hyaluronan complex significantly promotes the adhesion of leucocytes . Recent studies have revealed that ITIH5 expression is significantly upregulated in inflammatory skin diseases . In this study, we found that the PDCD5 and ITIH5 promoter regions were significantly hyperacetylated at histone H3 in sun‐exposed skin.…”
Section: Discussionmentioning
confidence: 49%
“…Moreover, during many inflammatory events, the ITIH–hyaluronan complex significantly promotes the adhesion of leucocytes . Recent studies have revealed that ITIH5 expression is significantly upregulated in inflammatory skin diseases . In this study, we found that the PDCD5 and ITIH5 promoter regions were significantly hyperacetylated at histone H3 in sun‐exposed skin.…”
Section: Discussionmentioning
confidence: 49%
“…A recent study also found that HC5 was the major heavy chain expressed in skin, predominantly due to its production by dermal fibroblasts (43). The authors conclude that HC5 may play an important role in inflammation through its interaction with HA.…”
Section: Discussionmentioning
confidence: 84%
“…Blots shown are representative of four experiments. Top, Western blot showing that the amount of I␣I heavy chain 5 present was markedly increased following stimulation with TGF␤1 Bottom, following TGF␤1 incubation, the cells were treated with 10 g/ml trypsin in PBS for 10 min at room temperature as shown previously to remove any cell surface/CD44-associated HA (43). C, cells were incubated with or without TGF␤1 (10 ng/ml) for 72 h. The cells were then either left untreated or exposed to Streptomyces hyaluronidase (0.4 units in 400 l of PBS for 2 h).…”
Section: Discussionmentioning
confidence: 99%
“…Although many of the mechanisms underlying the functional importance of IAIPs are not known, increases in IAIP expression are correlated with a diverse spectrum of pathological conditions including tissue injury and repair (Huth et al, 2015;Plaas et al, 2011;Tan, McGrouther, Day, Milner, & Bayat, 2011), and inflammation (Daveau et al, 1998;Garantziotis et al, 2007;Itoh et al, 1994;Kobayashi, 2006;Mizon, Mairie, Balduyck, Hachulla, & Mizon, 2001;Okroj et al, 2012;Seifert, Kurzinger, Hopt, & Wittel, 2013;Wakahara et al, 2005). Recent studies have also reported changes in the level of IAIPs after stroke (Kashyap et al, 2009) and Alzheimer's disease (Shi et al, 2019), suggesting that endogenous IAIPs may be integrally related to the pathogenesis of inflammatory-related brain disorders.…”
Section: Introductionmentioning
confidence: 99%